Single source precursor route for the first graphene oxide–Pd6P nanocomposite: application in electrochemical hydrogen evolution reaction. Issue 17 (20th April 2022) - Oswal, Preeti; Sood, Kritika; Singh, Siddhant; Arora, Aayushi; Bahuguna, Anurag; Purohit, Suraj; Kumar, Arun
Abstract : The first report of Pd6 P nanospheres synthesized via a single-source precursor route, further immobilized over graphene oxide sheets and explored for applications in electrochemical hydrogen evolution reaction. Abstract : For the first time, Pd6 P has been synthesised using a simple, straightforward and one-pot method i.e., thermolysis of a Pd(ii ) complex of a bidentate (P, N) organophosphorus ligand (anthracene-9-yl-CHN–CH2 CH2 –PPh2 ). The electrocatalyst (obtained after grafting nanospheres of Pd6 P over layers of graphene oxide) shows high activity in electrochemical hydrogen evolution reactions (HER) with an overpotential of 133 mV to drive 10 mA cm −2 of cathodic current density. The GO–Pd6 P nanocomposite is robust and effective for a continuous HER run for up to 16 hours.